Postmaidan Ukraine: Middle Class in the Shadow of Reforms - Aleksandrova, Olena; Dodonov, Roman; Vinnikova, Nataliia (Studia Warmińskie, 2019)
The article is devoted to the research of dynamics of the social structure of Ukrainian society in the period after the Revolution of Dignity in 2013-2014. The authors try to identify the leading tendencies of the middle class transformation, the basis for stability and guarantees of the irreversibility of democratic transformations in postmaidan Ukraine. The large-scale program of social transformation, proclaimed by the Ukrainian government (62 reforms), could not be implemented due to lack of essential resources, Russia's aggression in Donbas and an acute crisis of public trust to the government. The national middle class responded with quantitative reductions and qualitative changes in its composition. The factors influencing this process have been analyzed, in particular: the extraordinary concentration of large financial capital, genetically related to power; maintaining essential state regulation in the economy; increase of the share of social expenditures of the state in support for the lower stratum; increased migration activity of Ukrainians after obtaining a visa-free regime with the EU; social mobility in the labor market, precarization; reduction of working age rural population; influence of the informal (shadow) economy; decentralization of power; socio-political factors. It can be concluded that the middle class in postmaidan Ukraine has already realized its "social self," but cannot realize its activity-structural potential yet.